A comparative study of aquifer systems occurring at the Parana sedimentary basin, Brazil: major hydrochemical trends - Bonotto, Daniel Marcos [UNESP] (Springer, 2012)
This investigation was carried out within the Parana sedimentary basin, Brazil, and involved the sampling of 80 pumped tubular wells for evaluating the hydrochemistry in three aquifer systems (Bauru, Serra Geral and Guarani) occurring in 21 localities of So Paulo and Mato do Grosso Sul states. The Guarani aquifer of Triassic-Jurassic age has continental dimensions and extends over some 1.2 million km(2) within the Parana basin. A thick (up to 1,500 m) basaltic package of the Serra Geral Formation overlies this aquifer that is covered by Cretaceous sediments of the Bauru Group. Major hydrochemical data were obtained and compared in each aquifer system, allowing the establishment of the principal trends among the parameters analyzed. The redox potential Eh decreased according to the pH increase in the three aquifers. A consistent database has been assured from expected relationships found for typical parameters commonly evaluated in hydrogeochemical surveys. Thus, direct relationships of conductivity with ionic strength (IS) were determined and, despite bicarbonate, assumed an important role in justifying such trends; other direct significant correlations involving IS were also identified with Na+, Cl-, F- and SO4 (2-). Precipitation of carbonates was evidenced by opposite relations among CO3 (2-), Ca2+ and Mg2+ that are strongly linked to the temperature effects on Ca2+ and Mg2+ dissolution as often reported from theoretical constraints.
Keywords: Groundwater; Hydrochemistry; Parana sedimentary basin